Peran Dan Posisi Pemimpin Dalam Upaya Peningkatan Kualitas Sumber Daya Manusia - Putu Yulia Angga Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Human resources are a strategic component in the development of an organization. The development of an organization cant be separated from the role of human resources. Quality human resources are the basic capital in developing and realizing organizational goals effectively and efficiently. The quality of human resources, the central and most important point in an organization is related to the role, position and function of leadership in the organization with a leadership pattern that prioritizes professional principles and principles will easily lead the organization to grow and develop in accordance with the organization's vision and mission. In addition, leadership is an important instrument in the organization. This means that going forward or backward an organization cant be separated from the main role of leaders in influencing others and working together to achieve the goals that have been set.